Utilization of Learning Media Geography of High School in Sleman Regency - Supriyati, Supriyati (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
This study aims to explore various aspects of learning media in geography at senior high schools in Sleman Regency, focusing on four key areas: the availability of media (including type, quantity, and condition), the utilization of media, the difficulties faced by teachers, and the efforts made to optimize media use. Utilizing a descriptive quantitative method, the research surveyed geography teachers and high school students in grades X, XI, and XII across 45 schools, comprising 17 public and 28 private institutions. A proportional random sampling technique selected 16 schools, with 16 teachers and 96 students chosen through purposive sampling. Data were collected via questionnaires, interviews, and observations, and analyzed using descriptive statistical techniques. Results revealed that the available learning media, primarily maps, atlases, and globes, were classified as insufficient in quantity, despite being in good condition. The utilization of media was in a favorable category, with a media variation of 68.75 percent. Student responses regarding media usage were high, and opportunities for engagement were also positive. However, teachers faced significant challenges, with 68.75 percent reporting difficulties related to limited media availability, manpower, costs, and time. Teachers’ efforts to address these challenges were classified as moderate (87.50 percent), including organizing independent media, utilizing donations, and participating in training sessions and teacher meetings.